ส่วนประสมการตลาดที่มีอิทธิพลต่อการตัดสินใจซื้อน้ำดื่มบรรจุขวด ของผู้ประกอบการในเขตอำเภอเถิน จังหวัดลำปาง - ขวัญวงษ์ ภาณุพันธ์; น้อยทองเล็ก ธนกร (JOURNAL OF SOUTHERN TECHNOLOGY, 2016)
การศึกษามีวัตถุประสงค์เพื่อศึกษา (1) ระดับความคิดเห็นของส่วนประสมทางการตลาดและการตัดสินใจซื้อ และ (2) ส่วนประสมการตลาดที่มีอิทธิพลต่อการตัดสินใจซื้อน้ำดื่มบรรจุขวดของผู้ประกอบการในเขต อำเภอเถิน จังหวัดลำปาง ประชากร คือ ผู้บริโภคน้ำดื่มบรรจุขวดที่อาศัยอยู่ในเขตอำเภอเถิน จังหวัดลำปาง โดยวิธีการสุ่มตัวอย่างแบบสะดวก ได้กลุ่มตัวอย่างจำนวน 398 คน เป็นการวิจัยเชิงสำรวจ เครื่องมือที่ใช้คือ แบบสอบถาม ใช้สถิติพรรณนาในการวิเคราะห์ ได้แก่ ค่าความถี่ ค่าร้อยละ และค่าเบี่ยงเบนมาตรฐาน และสถิติอนุมานวิเคราะห์ความสัมพันธ์ของตัวแปรที่เกี่ยวข้องด้วยเทคนิคการถดถอยพหุคูณ ผลการวิจัยพบว่า ความคิดเห็นด้านส่วนประสมทางการตลาดโดยรวมอยู่ในระดับมากทุกปัจจัย ผลการทดสอบสมมติฐาน เรียงตามลำดับดังนี้ ด้านราคามีผลต่อการตัดสินใจซื้อสูงสุด ( =0.305, S.D.=0.57) คือ ด้านผลิตภัณฑ์ ( =0.283, S.D.=0.60) ด้านการส่งเสริมการตลาด ( =0.186, S.D.=0.50) และด้านการจัดจำหน่าย ( =0.100, S.D.=0.39) ตามลำดับ ซึ่งเป็นไปตามสมมติฐานอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 Effect of Marketing Mixes toward the Bottled Water Buying Decision of Entrepreneurs in Thoen District, Lampang Province The purposes of this research were to study the opinion level of marketing mixes, buying decision and the effect of marketing mixes toward the bottled water buying decision of entrepreneurs in Thoen district, Lampang province. The sampling group was 398 bottled water consumers in Thoen district by convenience sampling method. It was survey research with questionnaire as the research tool by applying descriptive statistics to find frequency, percentage, standard deviation and inferential statistics to analyze related variable correlations with multiple regression technique. The outcomes of research revealed that the majority of opinions toward marketing mixes were at high level on all factors. The hypothesis test revealed that price factor had the highest effect toward buying decision ( =0.305, S.D.=0.57) and followed by product factor ( =0.283 S.D.=0.60), marketing promotion factor ( =0.186, S.D.=0.50) and distribution factor ( =0.100 S.D.=0.39) subsequently which in line with hypothesis at .05 statistical significance level.